Diversity and morpho-agronomic characters of eggplant (Solanum sp) distributed in Palangka Raya Central Kalimantan - Hastin Ernawati Nur Chusnul Chotimah; Syahrudin Syahrudin; Wahyu Widyawati; Yusi Indriani; Kambang Vetrani Asie; Sri Endang Agustina Rahayuningsih (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
The eggplant species are currently at risk of extinction due to various factors such as land conversion into plantation areas and transmigration settlements in Palangka Raya. It is essential to conduct a thorough analysis of eggplant vegetation to address this urgent matter. Consequently, the research aimed to determine the diversity of eggplants, their distribution, as well as their morpho-agronomic characters. Field experiments were carried out in each district of Palangka Raya for 7 months. The methods used were survey, exploration, and interview with the key informant. Plant characterization refers to the descriptors for eggplant (IBPGR, 1990). The observed variables were the morphological characterization of eggplant, agronomy, and the distribution of eggplant in Palangka Raya. Results showed that it is found three species of eggplants, namely Solanum melongena (ungu, gelatik, telur, apel hijau eggplant cultivars), Solanum torvum, and Solanum ferox. There was variation in the morpho-agronomic characters of eggplant found.